2017
DOI: 10.3389/fnhum.2017.00066
|View full text |Cite
|
Sign up to set email alerts
|

Altered Intermittent Rhythmic Delta and Theta Activity in the Electroencephalographies of High Functioning Adult Patients with Autism Spectrum Disorder

Abstract: Background: Autism spectrum disorder (ASD) is often associated with epilepsy. Previous studies have also shown increased rates of electroencephalographic (EEG) alteration in ASD patients without epilepsy. The aim of this study was to compare the rate of intermittent rhythmic delta and theta activity (IRDA/IRTA) events between high-functioning adult patients with ASD and matched healthy controls.Materials and Methods: Routine EEG records of 19 ASD patients and 19 matched controls were screened for IRDA/IRTA usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
7
1
Order By: Relevance
“…The current study included one patient with comorbid epilepsy and epileptiform discharges, and 19% of the patients presented only focal or generalized slow activity. A previous study with a small sample size discerned a statistically significant difference between ASD patients and healthy controls in the rate of slow activity after hyperventilation [52]. One quarter of ASD patients in the current study showed nonspecific white matter alterations in their MRI.…”
Section: Eeg and Mri Findingscontrasting
confidence: 42%
“…The current study included one patient with comorbid epilepsy and epileptiform discharges, and 19% of the patients presented only focal or generalized slow activity. A previous study with a small sample size discerned a statistically significant difference between ASD patients and healthy controls in the rate of slow activity after hyperventilation [52]. One quarter of ASD patients in the current study showed nonspecific white matter alterations in their MRI.…”
Section: Eeg and Mri Findingscontrasting
confidence: 42%
“…However, all the alterations found in our patient were unspecific. In previous studies, antithyroid antibodies have been found in 13% of healthy adults [and even more often in females and older individuals ( 13 , 14 )]; EEG slowing was found in different psychiatric disorders [and infrequently in healthy controls ( 15 , 16 )]; a small number of cerebral hemispheric white matter lesions is a common incidental finding in healthy adults of this age ( 17 ). Only the patient’s responsiveness to plasmapheresis suggested the immunological cause.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an automated detection of intermittent generalized rhythmic delta/theta activity (IRDAs/IRTAs) was performed. The methodology has been described in the previous papers 29 , 30 , and the findings were divided into pre-HV-, post HV-, HV-difference (post-HV–pre-HV), and overall-IRDAs/IRTAS.…”
Section: Methodsmentioning
confidence: 99%